Figurative Language in Joel Osteen’s Speech “Your Words Become Your Reality” - Theresia Hutagalung; Muhammad Yusuf (Talenta Publisher, 2022)
This study attempts to explore figurative language in Joel Osteen's speech. This study employed a qualitative approach. The data of this research were from the utterances that occurred in the speech from the speech of Joel Osteen entitled